Peroxisome proliferator-activated receptor-γ as the gatekeeper of tight junction in Clostridioides difficile infection - Lai, Yi-Hsin; Wu, Tai-Chieh; Tsai, Bo-Yang; Hung, Yuan-Pin; Lin, Hsiao-Ju; Tsai, Yau-Sheng; Ko, Wen-Chien; Tsai, Pei-Jane (Frontiers in Microbiology, 2022)
Clostridioides difficile is a major causative pathogen of nosocomial antibiotic-associated diarrhea and severe colitis. Despite the use of vancomycin and fidaxomicin as standard drugs for the treatment of C. difficile infection (CDI), clinical relapse rates remain high. Therefore, new alternative therapeutics to treat CDI are urgently required. The nuclear receptor, peroxisome proliferator-activated receptor-γ (PPAR-γ), is mainly expressed in the adipose tissue and modulates lipid metabolism and insulin sensitization. Previous studies have shown that PPAR-γ is highly expressed in colonic tissues and regulates tight junction function in epithelial cells. However, the role of PPAR-γ in CDI pathogenesis remains unclear. In this study, we used a mouse model of CDI and found that both expression levels of PPAR-γ and the tight junction protein, occludin, were decreased in colonic tissues. Furthermore, to investigate the role of PPAR-γ in CDI, we used PPAR-γ defective mice and found that intestinal permeability and bacterial dissemination in these mice were significantly higher than those in wild-type mice during CDI. Administration of the PPAR-γ agonist, pioglitazone, to activate PPAR-γ activity improved the phenotypes of CDI, including bodyweight loss, inflammation, and intestinal integrity. Taken together, these results demonstrate that PPAR-γ is a potential therapeutic target in CDI, as it modulates colonic inflammation and integrity.